Deer Hunting Scene in the Decoration of the Clazomenian Sarcophagus from the Kunsthistorisches Museum in Vienna - Nenakhova, Maria N. (Actual Problems of Theory and History of Art, 2023)
The richly decorated terracotta sarcophagus (510 B. C.) from the Kunsthistorisches Museum in Vienna was found in Asia Minor, presumably in one of the Clazomenian necropolises. To date we are aware of about 200 Clazomenian sarcophagi. Their strictly regulated decorative system represents the same (with very few exceptions) compositional schemes (heraldic, symmetrical) and recurring images (hoplites, riders, chariots, mythical creature, animal friezes, etc.). However, one of the panels of the Clazomenian sarcophagus from Vienna presents an essentially different compositional scheme (open and dynamic) and the unique motive of a deer hunt with horses and chariots. In our opinion, the reason for this exclusive choice can be attributed to the artistic influence of the Achaemenid empire, which reflected common ideology of the regional elites.